PENGARUH PENERAPAN TEKNIK BISNIS BERISIKO TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN KOTO BARU DHARMASRAYA - Faridawati, Ida; Rahmi, Rahmi; Harisman, Yulyanti (STKIP PGRI Sumbar, 2014)
ABSTRACTThe background of this research is allow comprehension studentsâ mathematics concept and many students that are less responsible for the tasks from the teacher. The aim from this research is to know the comprehension studentsâ mathematics which uses Bisnis Berisiko Technique more better than the comprehension studentsâ mathematics which use a conventional learning at VIII grade students MTsN Koto Baru Dharmasraya.Â A kind of this research is experiment with random design to subject. The instrument is a comprehensions studentsâ mathematics test in the essay form with reliability of the test is . Based on analysis data obtained the average value of the experiment class higher than the control class. The hypothesis which use t-test, the result isÂ Â and , because of , so that the hypothesis research is accept. The conclusion from this research is the comprehension studentsâ mathematics which uses Bisnis Berisiko Technique more better than the comprehension studentsâ mathematics which use a conventional learning.